The world before us: reappraising globalization in education in the tumult of contemporary change - Goel, Koeli; Cai, Xiuying; Ogwal, Susan; Wong, Adrian; Engel, Laura C.; McCarthy, Cameron (Studies in the Cultural Politics of Education, 2020)
In reassessing globalization, contributors to this Special Issue collectively note the swirling, unstable set of forces that have followed in the wake of globalizing processes visited upon twenty-first century societies and their educational systems in the past few decades. As such, they write against dominant social science and policy understanding of globalization that insists on its unifying and universalizing tendency grounded in the affordances of the technological sublime of highspeed Internet, speeded-up communications and transportation putatively linking up the four corners of the globe and erasing boundaries of the North-South divide (Friedman, 2005). Particularly as educators, contributors insist that globalization is not an abstract or universalizing set of processes of time-space compression that absorb more and more of human reality into a singular homogenous space but is instead profoundly discriminatory and asymmetrical in its impact and effects. They maintain that globalization is now placing tremendous pressure on local settings and institutions such as schools and universities, on the very nature of intellectual and pedagogical processes, and on the social subjects and lived communities formed in these domains.
Keywords: World; Globalization; Education